Variation in Outpatient Antibiotic Dispensing for Respiratory Infections in Children by Clinician Specialty and Treatment Setting. Issue 12 (December 2018) - Agiro, Abiy; Gautam, Santosh; Wall, Eric; Hackell, Jesse; Helm, Mark; Barron, John; Zaoutis, Theoklis; Fleming-Dutra, Katherine E.; Hicks, Lauri A.; Rosenberg, Alan
Abstract : Background: Antibiotics are commonly prescribed for children with acute respiratory infections (ARIs). This study describes the distribution of ARI diagnoses and specifically quantifies antibiotic dispensing for bronchitis and upper respiratory infection (URI) by treatment setting and specialty. Methods: This retrospective, observational cross-sectional study used data from the HealthCore Integrated Research Environment containing claims from 14 commercial health plans for 2012 to 2014. Children (2–17 years) with first-episode ARI were identified by diagnosis of acute otitis media (AOM), sinusitis, pharyngitis, bronchitis or URI with no competing infections or chronic illnesses. Treatment setting was where diagnoses were made: primary care offices, urgent care centers (UCC), retail health clinics (RHCs) or emergency departments. Primary outcome measure was antibiotic prescription fills from pharmacies within 2 days of start of ARI episode. Results: For URI, the highest proportions in antibiotic dispensing were ordered by office-based or UCC family physicians (28% and 30%, respectively) and office-based or UCC nurse practitioners/physician assistants (30% and 29%, respectively). Across all settings and specialties, there was high proportion of antibiotic dispensing for bronchitis (75%). Overall, 48% of 544, 531 children diagnosed with ARI filled antibiotics. Nurse practitioners/physician assistants in RHC made the most diagnoses of AOM (24%) and streptococcal pharyngitis (22%). Conclusions: Outreach efforts to decrease antibiotic dispensing for URI can be focused on office-based and UCC family physicians and nurse practitioners/physician assistants. All specialties need widespread interventions to reduce antibiotic dispensing for bronchitis. RHC nurse practitioners/physician assistants can be targeted to reduce high proportion of AOM and streptococcal pharyngitis diagnoses. Abstract : Supplemental Digital Content is available in the text.